Physiology and Pathology of Immunology - Rezaei, Nima (IntechOpen, 2017)
Having authored and published many successful and important textbooks in primary immunodeficiencies and cancer immunology, the editor of Physiology and Pathology of Immunology has ensured the high standard of writing and authenticity of the contents in this publication. The current book covers a spectrum of high-impact knowledge on the complex interplay between the environment, genes, and immunity that culminates in a generation of notorious processes of immune-related disorders. From evolution of regulatory T-cell function, gigantic cytokine networks within the human body to host-pathogen interactions of Chagas disease and Parkinson's disease, the Physiology and Pathology of Immunology goes further to decipher new codes from the immunity enigma, making it essential for experienced and new learners who wish to join the galaxy of modern immunology.